Jenis Kelainan Artikulasi yang Paling Banyak Terjadi Pada Anak Dislogia Mental Retardasi - Yulidar Rusdi Rasyid; Agustina Agustina (Politeknik Arutala Johana Hendarto [d.h. Akademi Terapi Wicara], 2023)
When speaking, we interpret sound symbols or symbols spoken through the mouth, which is called articulation, whether the spoken word is produced clearly or not. This ability is influenced by the use of articulation organ movements. Good articulation if the speaker (communicant) when conveying what is said is heard or captured clearly by the other person (communicator), the speech does not sound good and does not experience failure or articulation errors, whether in the form of sound impressions (substitution), omission of sound (omission), sound disruption (distortion), and sound addition (addition). Dyslogia is a disorder of the mind caused by mental retardation, or intellectual disabilities whose intelligence is below average, which limits the normal IQ of 90. Children who have abnormalities or failure to produce articulations can be caused by abnormalities in the form of mental retardation, meaning that they are mentally retarded. Those with speech impairments are known as dyslogia. Mental retardation difficulties which are mainly in the form of difficulties in thinking and understanding. Life skills that can influence are certain conceptual, social and practical skills. The purpose of this research is to find out whether the most visible form of articulation failure is owned by clients with mental retardation dyslogia The research analyzed consisted of 10 (ten) samples which were secondary data, with forms of articulation failure in the form of substitution, omission, distortion and addition, also known as (SODA).